2007
DOI: 10.1158/1055-9965.epi-07-0116
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Is Associated with the Genes Encoding the DNA Double-Strand Break Repair Mre11/Rad50/Nbs1 Complex

Abstract: The evolutionarily conserved Mre11-Rad50-Nbs1 (MRN) complex, consisting of proteins encoded by the genes Mre11, Rad50, and Nbs1, was recently shown to play a crucial role in DNA double-strand break (DSB) repair by recruiting the nuclear protein kinase ataxia telangiectasia mutated to DSB sites, leading to activation of this DNA repair network. Given the fact that carriers of defective mutation and polymorphic variants of ataxia telangiectasia mutated are at higher risk of developing breast cancer, we hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 44 publications
3
49
1
Order By: Relevance
“…For example, MRE11A, a key component of the DNA mismatch repair pathway, functions in DNA double-strand break repair. It has been reported to accumulate somatic mutations that lead to truncations of its protein in many types of tumors, including breast cancer (16)(17)(18)(19)(20)(21)(22)(23)(24). In the HCC1954 cancer cell line, this gene is truncated at its DNA binding domain because of a translocation event between chromosomes 11 and 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, MRE11A, a key component of the DNA mismatch repair pathway, functions in DNA double-strand break repair. It has been reported to accumulate somatic mutations that lead to truncations of its protein in many types of tumors, including breast cancer (16)(17)(18)(19)(20)(21)(22)(23)(24). In the HCC1954 cancer cell line, this gene is truncated at its DNA binding domain because of a translocation event between chromosomes 11 and 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Publications on NBS1 polymorphisms have mainly focused on rs1805794 and the risk of cancers including lung, breast, bladder, renal cell cancers, non-Hodgkin lymphoma and childhood acute leukemia (Medina et al, 2003;Lan et al, 2005;Zienolddiny, 2005;Landi et al, 2006;Ryk et al, 2006;Hsu et al, 2007;Choudhury et al, 2008;Margulis et al, 2008;Mosor et al, 2008;Schuetz et al, 2009;Stern et al, 2009;Park et al, 2010), but the results were not consistent. A recent meta-analysis on rs1805794 has shed light on a positive association between the variant genotype of rs1805794 and the risk of multiple cancers (MeiXia et al, 2009).…”
Section: 851 Variants Of Nbs1 Predict Clinical Outcome Of Chemotheramentioning
confidence: 99%
“…Rs1805794 located in exon 5 of NBS1 is one of the most common polymorphisms and can induce an amino acid substitution from Glu to Gln. Studies have investigated the association between rs1805794 and risk of multiple cancers, such as lung, breast, bladder and nasopharyngeal carcinoma (Medina et al, 2003;Lan et al, 2005;Lu et al, 2006;Hsu et al, 2007;Stern et al, 2009;Zheng et al, 2011). However, only one study has explored the effect of this polymorphism on prognosis of human cancer and reported that it was not associated with the survival of esophagus or gastric adenocarcinoma after platinum-based neoadjuvant poly-chemotherapy (Ott et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…RAD genes are involved in DNA DSB repair and required for both (62,63) types of the repair processes, NHEJ and HR (60). Polymorphic variants and defective mutations of RAD50 may be at a risk of developing breast cancer possibly through the loss-of-function of the MRE11-RAD50-NBN complex, key factors in maintaining genome stability (61). Some patients with an HBOC-like phenotype have mutations in RAD50.…”
Section: Lynch Syndromementioning
confidence: 99%